Sound influence on spa park perception in feelings of visitors - Sztubecka, Małgorzata; Mrówczyńska, Maria; BazanKrzywoszańska, Anna; Skiba, Marta (International Conference “Environmental Engineering”, 2017)
Noise can have many harmful effects on the recipients, however people exposed to noise on a long erm and regular basis can get used to it, even if the permissible levels are exceeded. In cities, green areas and park systems are provided to create a climate for rest and relaxation. Spa parks are a special kind of such park systems, which – in addition to the above-mentioned features – support therapies offered by spa facilities located there. On the one hand, patients and visitors appreciate various social and entertainment events held there, but – on the other – a multitude of sounds associated with them may reduce the comfort of their stay. The aim of this paper is to analyse the relationship between the results of noise measurements and the human perception of noise within the impact zone. The examined area is a spa park in the health resort district of Inowrocław, where seasonal measurements (taken in summer and winter) provided a basis for the determination of the connection between the measured values of equivalent sound level and the noise level perceived by surveyed people. A statistical analysis was performed to take into account the correlation between the obtained measurement results and the human perception of noise. It shows some differences in the perception of heard sounds. The results allow an evaluation of the soundscape of the analysed area.
Keywords: acoustic climate; green area; noise; soundscape; spa park